Journey: o jogo e a experiência como fonte de criação - CARVALHO, Márcio Lins (Universidade Federal do Pará, 2017)
This dissertation discusses the experience with games (eletronic games), focused on case study that considers the analysis of the image, experience and mediation modes proposed by the game Journey (TGC, 2012). Therefore, there is the interactive, symbolic, interface and game functionality features in question and its aesthetic possibilities of dialogue with other art forms, such as comics and illustration. In this perspective, we make use of theories and authors that we consider relevant to the case study and relatable to important aspects in the approach of the game (Johan Huizinga, Roger Caillois, Eric Zimmerman, Katie Salen), imaginary (Gilbert Durand, Philippe Malrieu), experience in general and aesthetic experience in particular (Robert Solomon, John Dewey) and language and media (Lucia Santaella, Julio Plaza, Monica Tavares). Having the playful interaction as lens, it promotes an analysis of the intricacies of the game, its relations with the player(s), the questions posed during and at the end of his experience to thus understand how mimicry occurs with other means of expression that not only the game itself. The theoretical crossings tend to cooperate with the studies of the game while expanded field of art.